More Than Inconvenienced: The Unique Needs of U.S. College Students During the COVID-19 Pandemic - Lederer, Alyssa M.; Hoban, Mary T.; Lipson, Sarah K.; Zhou, Sasha; Eisenberg, Daniel (Health education & behavior, 2021)
U.S. college students are a distinct population facing major challenges due to the COVID-19 pandemic. Before the pandemic, students were already experiencing substantial mental health concerns, putting both their health and academic success in jeopardy. College students now face increasing housing and food insecurity, financial hardships, a lack of social connectedness and sense of belonging, uncertainty about the future, and access issues that impede their academic performance and well-being. There is also reason to believe that COVID-19 is exacerbating inequalities for students of color and low-income students. We provide several recommendations for institutions of higher education to mitigate these obstacles, including engaging in data-driven decision making, delivering clear and informative messaging to students, prioritizing and expanding student support services, and using an equity framework to guide all processes.